2015
DOI: 10.1186/s12879-015-0762-x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic profiling of CD8+ T cells during Plasmodium vivax blood-stage infection

Abstract: BackgroundFor a long time, the role of CD8+ T cells in blood-stage malaria was not considered important because erythrocytes do not express major histocompatibility complex (MHC) class I proteins. While recent evidences suggest that CD8+ T cells may play an important role during the erythrocytic phase of infection by eliminating parasites, CD8+ T cells might also contribute to modulate the host response through production of regulatory cytokines. Thus, the role of CD8+ T cells during blood-stage malaria is unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…The reduction among those subpopulations was also evident in other studies carried out with P. vivax naturally infected individuals [55, 59, 63, 64]. Those authors interpreted the reduction in the lymphocyte subpopulations in the peripheral blood as a suppressant effect in the response to the P. vivax [55, 56, 6365]. According to them, such reduction could be due to the high apoptosis levels or to the relocation of the cells in the liver and in other lymphoid compartments [55, 64, 6668].…”
Section: Discussionsupporting
confidence: 76%
“…The reduction among those subpopulations was also evident in other studies carried out with P. vivax naturally infected individuals [55, 59, 63, 64]. Those authors interpreted the reduction in the lymphocyte subpopulations in the peripheral blood as a suppressant effect in the response to the P. vivax [55, 56, 6365]. According to them, such reduction could be due to the high apoptosis levels or to the relocation of the cells in the liver and in other lymphoid compartments [55, 64, 6668].…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, vivax malaria patients have shown significant low RANTES/CCL5 levels, but just weakly associated with IL-6, IL-12p40, IFN-γ or MCP-1/CCL2. The lower levels of RANTES/CCL5 could be explained by the CD8 + T cells reduction [4345] and thrombocytopaenia [8, 10, 11, 4446] observed during vivax malaria. A study carried out with children infected with P. falciparum observed an association between thrombocytopaenia and lower RANTES plasma levels [47].…”
Section: Discussionmentioning
confidence: 99%
“…The primary antibodies for IL-33 (sc-130625), HBx (sc-57760) and GAPDH (sc-32233), in addition to the goat anti-mouse IgG horseradish peroxidase-conjugated secondary antibody (sc-2302) were all purchased from Santa Cruz Biotechnology, Inc. 28; PBMCs were isolated. Subsequently, the proportional changes of naïve T cells (TN; CD45RA+CCR7+), central memory T cells (TCM; CD45RA-CCR7+) and effector memory T cells (TEM; CD45RA-CCR7-) were assessed (29,30). As presented in Fig.…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 99%